Etude math ́ematique d’un probl`eme aux limites avec r ́eponse amortie normale et endommagement - Selssabila, LACHRAF; Mouna, GHENBAZI (My University, 2022)
نحن نعتبر مشكلة التلامس الاحتكاكیة شبه الساكنة بین الجسم المرن اللزج والعائق. تم تصمیم جهة الاتصال مع استجابة مخففة طبیعیة وقانون احتكاك محلي. المادة عبارة عن بلاستیك مرن - لزج مع متغیرین داخلیین قد یصفان معامل درجة الحرارة وتلف السطح الملامس. نحن نقدم صیاغة متغیرة للمشكلة ونثبت وجود حل ضعیف فرید للنموذج. یعتمد الدلیل على حجج معادلات التطور باستخدام عوامل أحادیة ، وجود كلاسیكي و نتیجة فریدة على عدم المساواة في القطع المكافئ والنقطة الثابتة.We consider a quasistatic frictional contact problem between an elastic-viscoplastic body and an obstacle. The contact is modelled with normal damped response and a local friction law. The material is elastic-viscoplastic with two internal variables which may describe a temperature parameter and the damage of the contacting surface. We provide a variational formulation of the problem and prove the existence of a unique weak solution to the model. The proof is based on arguments of evolution equations with monotone operators, a classical existence and uniqueness result on parabolic inequalities and fixed
mémoire mastre mathématiques
Keywords: مواد لدائن حراریة مرنة ؛ عملیة شبه ثابتة ؛ اتصال احتكاكي ؛ مجال الضرر ؛ استجابة مخففة طبیعیة ؛ نقطة ثابتة.; Thermo-elastic-viscoplastic materials; Quasistatic process; Frictional contact; Damage field; Normal damped response; Fixed point.